La Biblia vaquera: frontera y juego - Chiara Lippi (Confluenze, 2020)
Within the Northern Mexican Literature, a new generation of writers has emerged, disenfranchised from prototypical northern elements: the border, violence and drug trafficking. La Biblia Vaquera stands out for its emblematic postmodern experimentation. By analyzing Velázquez’s wordplays, this paper aims at highlighting the norteño literary space which does not identify with borderland dynamics, but with game as an act of creating reality, as well as a postmodernist antidote against the delegitimation of Knowledge (Lyotard, 2018).